(untitled) (Acta Entomológica Chilena, 2022)
The information available about the 20 species known from Chile, which belong to 13 genera and 3 subfamilies. The recently introduction of Chrysomya albiceps (Wiedemann) to our country is included. The sanitary importance of these flies and the lack of information about the distribution in our territory is discussed.